Mothers’ Insistence when Prohibiting Infants from Harming Others in Everyday Interactions - Dahl, Audun (Frontiers in Psychology, 2016)
Social interactions about transgressions provide a context for the development of children’s moral aversion to harming others. This study investigated mothers’ insistence when communicating the prohibition against harming others to infants in everyday home interactions. Mothers’ reactions to infants’ use of force against others (moral harm transgressions) were compared to their reactions to transgressions pertaining to infant wellbeing (prudential) and transgressions pertaining to inconvenience (pragmatic). Twenty-six infants and their families participated in 2.5-hour naturalistic home observations when infants were 14, 19, and 24 months old. Mothers’ interventions on moral harm transgressions involved increased use of physical interventions and direct commands, and decreased use of distractions, softening interventions, and relenting/compromising, compared to their interventions on prudential and pragmatic transgressions. Children showed the greatest immediate compliance with, and least protests against, maternal interventions on moral harm transgressions.